2013
DOI: 10.19026/rjaset.6.3672
|View full text |Cite
|
Sign up to set email alerts
|

Handling Intrusion Detection System using Snort Based Statistical Algorithm and Semi-supervised Approach

Abstract: Intrusion detection system aims at analyzing the severity of network in terms of attack or normal one. Due to the advancement in computer field, there are numerous number of threat exploits attack over huge network. Attack rate increases gradually as detection rate increase. The main goal of using data mining within intrusion detection is to reduce the false alarm rate and to improve the detection rate too. Machine learning algorithms accomplishes to solve the detection problem. In this study, first we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Based on the performance of the system, it showed that hybridised SSO-WLS is one of the competitive classifiers that can be used in IDS development. [Nadiammai and Hemalatha, (2013)] presented data mining-based techniques for hybrid IDS using the combination of snort based statistical and semi-supervised classification algorithm was used in training 2500 data instances. The experimental results were conducted using KDD Cup'99 dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the performance of the system, it showed that hybridised SSO-WLS is one of the competitive classifiers that can be used in IDS development. [Nadiammai and Hemalatha, (2013)] presented data mining-based techniques for hybrid IDS using the combination of snort based statistical and semi-supervised classification algorithm was used in training 2500 data instances. The experimental results were conducted using KDD Cup'99 dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are two basic types of intrusion detection based on the range of its detection: host-based and network-based [15] while [19] classified intrusion detection into three including Vulnerability-Assessment i.e Vulnerable attacks are to detect on internal networks and firewalls as the third attack. Each has a distinct approach to monitoring and securing data, and each has distinct advantages and disadvantages, host-based IDSs examine data held on individual computers that serve as hosts, while network-based IDSs examine data exchanged between computers.…”
Section: Introductionmentioning
confidence: 99%